The Distinct Transcriptional Response of the Midgut of Amblyomma sculptum and Amblyomma aureolatum Ticks to Rickettsia rickettsii Correlates to Their Differences in Susceptibility to Infection - Andréa C. Fogaça; Larissa A. Martins; Maria F. B. de Melo Galletti; José M. Ribeiro; André Fujita; Francisco B. Costa; Marcelo B. Labruna; Sirlei Daffre (Frontiers in Cellular and Infection Microbiology, 2017)
Rickettsia rickettsii is a tick-borne obligate intracellular bacterium that causes Rocky Mountain Spotted Fever (RMSF). In Brazil, two species of ticks in the genus Amblyomma, A. sculptum and A. aureolatum, are incriminated as vectors of this bacterium. Importantly, these two species present remarkable differences in susceptibility to R. rickettsii infection, where A. aureolatum is more susceptible than A. sculptum. In the current study, A. aureolatum and A. sculptum ticks were fed on suitable hosts previously inoculated with R. rickettsii, mimicking a natural infection. As control, ticks were fed on non-infected animals. Both midgut and salivary glands of all positively infected ticks were colonized by R. rickettsii. We did not observe ticks with infection restricted to midgut, suggesting that important factors for controlling rickettsial colonization were produced in this organ. In order to identify such factors, the total RNA extracted from the midgut (MG) was submitted to next generation RNA sequencing (RNA-seq). The majority of the coding sequences (CDSs) of A. sculptum differentially expressed by infection were upregulated, whereas most of modulated CDSs of A. aureolatum were downregulated. The functional categories that comprise upregulated CDSs of A. sculptum, for instance, metabolism, signal transduction, protein modification, extracellular matrix, and immunity also include CDSs of A. aureolatum that were downregulated by infection. This is the first study that reports the effects of an experimental infection with the highly virulent R. rickettsii on the gene expression of two natural tick vectors. The distinct transcriptional profiles of MG of A. sculptum and A. aureolatum upon infection stimulus strongly suggest that molecular factors in this organ are responsible for delineating the susceptibility to R. rickettsii. Functional studies to determine the role played by proteins encoded by differentially expressed CDSs in the acquisition of R. rickettsii are warranted and may be considered as targets for the development of strategies to control the tick-borne pathogens as well as to control the tick vectors.